2018
DOI: 10.1101/417881
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proximal perimeter encoding in the rat rostral thalamus

Abstract: Perimeters are an important part of the environment, delimiting its geometry. Here, we investigated how perimeters (vertical walls; vertical drops) affect neuronal responses in the rostral thalamus (the anteromedial and parataenial nuclei in particular). We found neurons whose firing patterns reflected the presence of walls and drops, irrespective of arena shape. Their firing patterns were stable across multiple sleep-wake cycles and were independent of ambient lighting conditions. Thus, rostral thalamic nucle… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Accordingly, a picture of a distributed network of interconnected regions with egocentric vector representations is beginning to emerge. Given the presence of EBCs in several midline structures, it is possible that EBCs are also present in the anterior cingulate cortex as well as thalamic structures that innervate midline associative cortex (Weible et al, 2012; Matulewicz et al, 2019). Future investigations should focus on dependencies amongst the regions currently implicated, as the EBC network may possess functional and anatomical connectivity resembling the well-characterized extended head direction cell network (Taube et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a picture of a distributed network of interconnected regions with egocentric vector representations is beginning to emerge. Given the presence of EBCs in several midline structures, it is possible that EBCs are also present in the anterior cingulate cortex as well as thalamic structures that innervate midline associative cortex (Weible et al, 2012; Matulewicz et al, 2019). Future investigations should focus on dependencies amongst the regions currently implicated, as the EBC network may possess functional and anatomical connectivity resembling the well-characterized extended head direction cell network (Taube et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The grid-like signal found in these regions could, therefore, be thalamic rather than entorhinal in origin. In addition to the head-direction cells in the anterodorsal thalamic nucleus, the anteroventral nucleus possesses theta-modulated head-direction cells (Tsanov et al, 2011), while the anteromedial nucleus contains place cells and perimeter/boundary cells (Jankowski et al, 2015;Matulewicz et al, 2019). Bonnavie et al (2013) demonstrated that when the hippocampus was inactivated with muscimol, entorhinal grid cells lost their periodicity resulting in head direction cells.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, for instance, anterior thalamic lesions severely impair spatial learning, echoing the effects of hippocampal damage (Morris et al, 1982;Sutherland and Rodriguez, 1989;Moran and Dalrymple-Alford, 2003), with disconnection studies confirming the interdependence of the hippocampal formation and anterior thalamus (Warburton et al, 2000(Warburton et al, , 2001Henry et al, 2004). Moreover, neuronal recordings within the ATN show the presence of place, head direction and border cells (Taube, 1995;Jankowski et al, 2015;Matulewicz et al, 2019), suggesting the ATN is also a spatial processing node. Outstanding questions include whether any hippocampal formation spatial functions are dependent on the ATN and, if so, why.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…(The one possible exception concerns the appreciation that the anterodorsal thalamic nucleus contains headdirection cells; 2007). Unexpectedly, there are cells in all of these regions that code for aspects of three-dimensional space, including positional information, boundary or perimeter information, as well as head directional and object information (Jankowski et al, 2014;2015;2017;Jankowski and O'Mara, 2015;Matulewicz et al, 2019). Moreover, it is now clear that lesions of the rostral and anterior thalamic nuclei can result in deficits in the performance of spatial and non-spatial tasks that appear comparable to those resulting from lesions within the entorhinal-hippocampal axis.…”
Section: Introductionmentioning
confidence: 99%